Assessment of quality of prescription by dental students (Journal of Applied Oral Science, 2014)
Objective: The main objective of this study was to evaluate changes in prescribing pattern of Dentistry students throughout academic course. Methods: A case of non-complicated dental extraction was presented to all students that had completed their pharmacology coursework (from 4th semester to the last semester). The students were grouped according to year of study and were asked to prescribe paracetamol for pain control. A maximal score of 5 points was calculated from three subscores for identification of professional and patient (1.0 point), drug concentration, dosage, and quantity (1.5 points); and drug information, instructions, and warnings (2.5 points). The data were expressed as medians [95% confidence intervals (CIs)] and were compared using the Kruskal-Wallis test followed by Dunn's post hoc test. A p